The Potential Role of Genetics, Environmental Factors, and Gut Dysbiosis in the Aberrant Non-Coding RNA Expression to Mediate Inflammation and Osteoclastogenic/Osteogenic Differentiation in Ankylosing Spondylitis - Liao, Hsien-Tzung; Tsai, Chang-Youh; Lai, Chien-Chih; Hsieh, Song-Chou; Sun, Yi-Syuan; Li, Ko-Jen; Shen, Chieh-Yu; Wu, Cheng-Han; Lu, Cheng-Hsun; Kuo, Yu-Min; Li, Tzu-Hao; Chou, Chung-Tei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Ankylosing spondylitis (AS) or radiographic axial spondyloarthritis is a chronic immune-mediated rheumatic disorder characterized by the inflammation in the axial skeleton, peripheral joints, and soft tissues (enthesis, fascia, & ligament) associated with extra-skeletal complications including anterior uveitis, interstitial lung fibrosis, or aortitis. The pathogenesis of AS implicates an intricate interaction \among genetic factors (human leukocyte antigen [HLA]-B27 and non-major histocompatibility complex [MHC] loci, endoplasmic reticulum aminopeptidase 1 [ERAP1], & interleukin-23 receptor [IL23R]), gut dysbiosis, immune plasticity, and numerous environmental factors (infections, heavy metals, stress, cigarette smoking, etc.). The latter multiple non-genetic factors may exert a powerful stress on epigenetic regulations including DNA methylation/demethylation, histone modifications and non-coding RNA (ncRNA) expression to result in devastating inflammation. In the present review, we would discuss in detail these factors, especially the aberrant ncRNA expression and its ensuing deviation of signaling pathways, as well as their effect on the proinflammatory cytokines (TNF-, IL-17, & IL-23), T cell skewing to Th1/Th17, and osteogenic/osteoclastogenic differentiation. Finally, we would also raise some open questions and respective potential investigatory approaches to solve them in order to further understand AS.